ARAB SPRING: PERUBAHAN REZIM DAN TEGANGAN HUBUNGAN AS – DUNIA ARAB REFLEKSI SOSIO-HISTORIS - Herdi Sahrasad (Arabic Literature Department, 2013)
The revolutions in the Arab World such as Egypt, Tunisia, Marocco, Libya, Syriaand Yemen have affected political landscapes in the Middle East countries. Revolutionsin the MENA countries have broken up relations between the Arab World and the US.The revolutions also have paved the way for Islamic groups to put political pressures totake power . Moreover, the Arab Spring have the influence over changes in the UnitedStates foreign policy in Middle East. But, up to now, it is not clear that the revolution in the Middle East in 2011 is agreat opportunity for the U.S. to increase its role in countries. It's not clear too, whetheror not it also a new opportunity for the U.S. to establish strategic alliances in ArabicWorld. While Washington was surprised by the fall of the regimes of Egypt and Tunisia, for instance, there is uncertainty that the two countries would be the new alliances ofthe US in the near future. America has lost its loyalists such as former Egyptian President Hosni Mubarakand Ben Ali, Tunis. But at the same time, the proximity of the the US-Gulf alliances isincreasing, especially with Saudi Arabia,Bahrain, Kuwait and Qatar . Washington for awhile is still groping, if not frenzy, in rebuilding the present relationship with the MiddleEast, as long as the MENA countries are still in the era of transition. The U.S and theWest are aware about that problem, and they understand that in the Middle East thepolitical uncertainty is so apparently.